Psychometric Validation of the Academic Motivation Scale in a Dental Student Sample. Issue 8 (1st August 2015) - Orsini, Cesar; Binnie, Vivian; Evans, Phillip; Ledezma, Priscilla; Fuentes, Fernando; Villegas, Maria J.
Abstract : The Academic Motivation Scale is one of the most frequently used instruments to assess academic motivation. It relies on the self‐determination theory of human motivation. However, motivation has been understudied in dental education. Therefore, to address the lack of valid instruments to assess academic motivation in dental education and contribute to future research in the field, the aim of this study was to analyze the psychometric properties of this instrument in a sample of dental students. Participants were 989 Chilean undergraduate dental students (86% response rate) who completed a survey containing a Chilean face‐valid version of the Spanish Academic Motivation Scale and three other motivation‐related instruments to assess the survey's construct and criterion validity. Later, 76 of the students (out of 100 invited) took the survey again to assess its test‐retest stability. The instrument's construct validity was supported by the superior goodness of fit of the seven‐subscale Academic Motivation Scale over competing models through confirmatory factor analysis and by the expected correlations among its subscales. The concurrent criterion validity was supported by the confirmation of correlations between its subscales and external criteria. Adequate internal consistency and test‐retest correlations were also found. The evidence from this study suggests that the Academic Motivation Scale is a preliminarily valid and reliable instrument to assess motivation in the predoctoral dental context. Future research in this area is needed to confirm or refute these results.